3D Digital Simulation System of Power Transmission and Transformation Line based on Digital Twin - Han, Xu; Yang, Huanjun (International Journal of Mechanical and Electrical Engineering, 2025)
In view of the problem that the original system cannot truly display the geographical environment of engineering, the design method of the 3D digital system of power transmission line based on digital twin is studied. In the hardware design, the transmission line network architecture is arranged, embedded in the OPC-UA server, and the sensor node location is bound. In the software design, the spatial database of transmission and transformation lines is established, the digital twin 3D virtual model is constructed, and the design of 3D digital system is completed. With complex area transmission and transformation line construction project as the object of experiment, the experimental results show that: select the location of the multiple scenarios line segment distance measurement, two groups of traditional methods to the actual distance measurement error, generated topographic map deformation, and the system can completely restore the transmission line segment distance, has the practical application effect.